Oseltamivir Use Among Children and Adults Hospitalized With Community-Acquired Pneumonia. (27th December 2016) - Oboho, Ikwo K.; Bramley, Anna; Finelli, Lyn; Fry, Alicia; Ampofo, Krow; Arnold, Sandra R.; Self, Wesley H.; Williams, Derek J.; Courtney, D. Mark; Zhu, Yuwei; Anderson, Evan J.; Grijalva, Carlos G.; et al.
Abstract: Background: Data on oseltamivir treatment among hospitalized community-acquired pneumonia (CAP) patients are limited. Methods: Patients hospitalized with CAP at 6 hospitals during the 2010−2012 influenza seasons were included. We assessed factors associated with oseltamivir treatment using logistic regression. Results: Oseltamivir treatment was provided to 89 of 1627 (5%) children (<18 years) and 143 of 1051 (14%) adults. Among those with positive clinician-ordered influenza tests, 39 of 61 (64%) children and 37 of 48 (77%) adults received oseltamivir. Among children, oseltamivir treatment was associated with hospital A (adjusted odds ratio [aOR], 2.76; 95% confidence interval [CI], 1.36−4.88), clinician-ordered testing performed (aOR, 2.44; 95% CI, 1.47−5.19), intensive care unit (ICU) admission (aOR, 2.09; 95% CI, 1.27−3.45), and age ≥2 years (aOR, 1.43; 95% CI, 1.16−1.76). Among adults, oseltamivir treatment was associated with clinician-ordered testing performed (aOR, 8.38; 95% CI, 4.64−15.12), hospitals D and E (aOR, 3.46−5.11; 95% CI, 1.75−11.01), Hispanic ethnicity (aOR, 2.06; 95% CI, 1.18−3.59), and ICU admission (aOR, 2.05; 95% CI, 1.34−3.13). Conclusions: Among patients hospitalized with CAP during influenza season, oseltamivir treatment was moderate overall and associated with clinician-ordered testing, severe illness, and specific hospitals. Increased clinician education is needed to include influenza in the differential diagnosis for hospitalized CAP patients and to test and treat patients empirically if influenza is suspected.